Aging diminishes the resistance of AO rats to EAE: putative role of enhanced generation of GM-CSF Expressing CD4+ T cells in aged rats. Issue 1 (December 2015) - Stojić-Vukanić, Zorica; Nacka-Aleksić, Mirjana; Pilipović, Ivan; Vujnović, Ivana; Blagojević, Veljko; Kosec, Duško; Dimitrijević, Mirjana; Leposavić, Gordana
Abstract Background Aging influences immune response and susceptibility to EAE in a strain specific manner. The study was designed to examine influence of aging on EAE induction in Albino Oxford (AO) rats. Results Differently from 3-month-old (young) rats, which were resistant to EAE induction, the majority of aged (24-26-month-old) rats developed mild chronic form of EAE. On 16th day post-immunization, when in aged rats the neurological deficit reached plateau, more mononuclear cells, including CD4+ T lymphocytes was retrieved from spinal cord of aged than young rats. The frequencies of IL-17+ and GM-CSF+ cells within spinal cord infiltrating CD4+ lymphocytes were greater in aged rats. To their increased frequency contributed the expansion of GM-CSF + IL-17 + IFN-γ+ cells, which are highly pathogenic in mice. The expression of the cytokines (IL-1β and IL-23/p19) driving GM-CSF + IL-17 + IFN-γ + cell differentiation in mice was also augmented in aged rat spinal cord mononuclear cells. Additionally, in aged rat spinal cord the expansion of GM-CSF + IL-17-IFN-γ- CD4+ T lymphocytes was found. Consistently, the expression of mRNAs for IL-3, the cytokine exhibiting the same expression pattern as GM-CSF, and IL-7, the cytokine driving differentiation of GM-CSF + IL-17-IFN-γ- CD4 + lymphocytes in mice, was upregulated in aged rat spinal cord mononuclear cells, and the tissue, respectively. This was in accordance with the enhanced generation of the brain antigen-specific GM-CSF+ CD4+ lymphocytes in aged rat draining lymph nodes, as suggested by (i) the higher frequency of GM-CSF+ cells (reflecting the expansion of IL-17-IFN-γ- cells) within their CD4+ lymphocytes and (ii) the upregulated GM-CSF and IL-3 mRNA expression in fresh CD4+ lymphocytes and MBP-stimulated draining lymph node cells and IL-7 mRNA in lymph node tissue from aged rats. In agreement with the upregulated GM-CSF expression in aged rats, strikingly more CD11b + CD45int (activated microglia) and CD45hi (mainly proinflammatory dendritic cells and macrophages) cells was retrieved from aged than young rat spinal cord. Besides, expression of mRNA for SOCS1, a negative regulator of proinflammatory cytokine expression in innate immunity cells, was downregulated in aged rat spinal cord mononuclear cells. Conclusions The study revealed that aging may overcome genetic resistance to EAE, and indicated the cellular and molecular mechanisms contributing to this phenomenon in AO rats.